Preliminary study on trace elements distribution and electron density variation in canine mammary tissues using a synchrotron-based micro X-ray fluorescence system. (October 2022) - Salvego, C.A.; Antoniassi, M.; Oliveira, N.M.P.; Burille, F.; Sousa, R.S.; Conceição, A.L.C.
Abstract: Mammary neoplasms are the most common in female dogs, with high malignancy rates. Despite sharing many similarities with human breast tissues, the prevalence of this type of cancer in dogs are nearly three times higher. Taking that into account, this study aims to present preliminary results about chemical and structural changes occurring in samples of canine breast tumors. For this, we analyzed seven samples including normal, benign and malignant tissues, using micro X-ray fluorescence ( μ -XRF) and Compton scattering technique. Our goal was to respectively map the spatial distribution of Fe, Cu and Zn and to determine the electron densities in selected regions of the samples. Results showed that Cu and Zn distributions were spatially correlated in normal tissues, with lower intensities in adipose regions and higher in the fibrous ones. Regarding benign neoplasms, both samples exhibited an increase in Cu intensity over the tumor area, however in different proportions. For the malignant ones, the presence of Fe was observed mostly in the tumor-adjacent regions. The electron density values obtained allowed to differentiate tissue structures, with generally higher density in tumorous regions and lower in adipose tissues. Highlights: Health and tumoral canine breast samples were analyzed using synchrotron radiation. Micro-XRF and Compton scattering techniques were combined. Micro-XRF provided the spatial distribution of Fe, Cu and Zn in the samples. Compton scattering was sensitive to variations of electron densities in the samples.